2013
DOI: 10.1111/jzo.12018
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns and temporal avoidance by prey in response to Sunda clouded leopard predation risk

Abstract: Little is known about the activity patterns of Bornean ungulates, or the temporal interactions of these species with the Sunda clouded leopard Neofelis diardi. In this study, we use photographic capture data to quantify the activity patterns for the Sunda clouded leopard and six potential prey species: bearded pig Sus barbatus, Bornean yellow muntjac Muntiacus atherodes, red muntjac Muntiacus muntjak, lesser mouse deer Tragulus kanchil, greater mouse deer Tragulus napu, and sambar deer Rusa unicolor, and to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 30 publications
3
96
0
2
Order By: Relevance
“…To reduce bias caused by repeated records of the same animal due to the proximity of some cameras (cameras placed 500 m apart), we only used the first record per hour per camera site as a detection event for each 24 h period, and the remaining records were eliminated from the analysis (Ross et al, 2013). We classified observations as diurnal (if activity was predominantly between 1 hour after sunrise and 1 hour before sunset), nocturnal (if activity was predominantly between 1 hour after sunset and 1 hour before sunrise), and crepuscular (if activity occurred up to 1 hour before and after sunrise and sunset).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce bias caused by repeated records of the same animal due to the proximity of some cameras (cameras placed 500 m apart), we only used the first record per hour per camera site as a detection event for each 24 h period, and the remaining records were eliminated from the analysis (Ross et al, 2013). We classified observations as diurnal (if activity was predominantly between 1 hour after sunrise and 1 hour before sunset), nocturnal (if activity was predominantly between 1 hour after sunset and 1 hour before sunrise), and crepuscular (if activity occurred up to 1 hour before and after sunrise and sunset).…”
Section: Discussionmentioning
confidence: 99%
“…These studies are based on the assumption that predators may tailor their activity to that of their potential prey to increase the probability of encounters, thereby reducing the energy expended in capturing prey (Emmons, 1987;Foster et al, 2013;Harmsen et al, 2011). In response, it has also been reported that prey may alter their foraging times to avoid predators (Harmsen et al, 2011;Ross et al, 2013). Most such studies have focused on the interactions of larger felids (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Ross et al. ). In this situation, the third species may introduce spurious relationships between focal species that in reality is caused by interactions with the third species.…”
Section: Discussionmentioning
confidence: 99%
“…An interval of 24 h between records was given in order to guarantee independence of records of the same species. This premise was not followed when it was possible to identify different individuals, in which case each one was considered an independent record (Ross et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Because of the proximity of camera traps in the first, fourth and sixth survey, only the first record per hour per camera site was used as a detection event in each 24 h period. The remaining records were eliminated from the analysis to reduce bias (Ross et al, 2013). Then, the time of each picture was converted to solar time (Foster et al, 2013;Porfirio et al, 2016a), and observations were classified as diurnal (activity predominantly between 1 h after sunrise and 1 h before sunset), nocturnal (activity predominantly between 1 h after sunset and 1 h before sunrise) or crepuscular (period that last 1 h before to 1 h after sunrise and sunset) following Romero-Muñoz et al (2010).…”
Section: Nature Conservation Research заповедная наука 2018 3(2): 5mentioning
confidence: 99%